Reusability of software-defined networking applications: A runtime, multi-controller approach - Doriguzzi Corin, Roberto; A. Aranda-Gutierrez, Pedro; Rojas, Elisa; Karl, Holger; Salvadori, Elio (12th International Conference on Network and Service Management, CNSM 2016, Montreal, QC, Canada, October 31 - Nov. 4, 2016)

Understand Your Chains: Towards Performance Profile-Based Network Service Management - Peuster, Manuel; Karl, Holger (Fifth European Workshop on Software-Defined Networks, EWSDN 2016, Den Haag, The Netherlands, October 10-11, 2016)
Allocating resources to virtualized network functions and services to meet service level agreements is a challenging task for NFV management and orchestration systems. This becomes even more challenging when agile development methodologies, like DevOps, are applied. In such scenarios, management and orchestration systems are continuously facing new versions of functions and services which makes it hard to decide how much resources have to be allocated to them to provide the expected service performance. One solution for this problem is to support resource allocation decisions with performance behavior information obtained by profiling techniques applied to such network functions and services. In this position paper, we analyze and discuss the components needed to generate such performance behavior information within the NFV DevOps workflow. We also outline research questions that identify open issues and missing pieces for a fully integrated NFV profiling solution. Further, we introduce a novel profiling mechanism that is able to profile virtualized network functions and entire network service chains under different resource constraints before they are deployed on production infrastructure.

Demonstrating on-demand cell switching with a two-layer mobile network testbed - Peuster, Manuel; Karl, Holger; Enrico Redondi, Alessandro; Capone, Antonio (IEEE Conference on Computer Communications Workshops, INFOCOM Workshops 2016, San Francisco, CA, USA, April 10-14, 2016)
Traditional cellular networks are forced to remain active regardless of the actual amount of traffic that is currently produced/requested, with a clear waste of energy. Two-layer mobile networks with separated signalling and data layers have been recently proposed for energy savings in future implementations. These networks are able to switch off unneeded data cells completely while maintaining full coverage with their signalling cells, thus saving energy. In this demonstration, we showcase a testbed that uses Wi-Fi access points to emulate small cells of the data layer and a publicly available cellular connection as the signalling layer. We use off-the-shelf Android smartphones with an ad-hoc networking management module and a MultiPath TCP-enabled kernel to manage the Wi-Fi and cellular interfaces simultaneously. The testbed is used to demonstrate the general feasibility of this layered architecture and to facilitate experiments with network-wide resource optimization.

E-State: Distributed state management in elastic network function deployments - Peuster, Manuel; Karl, Holger (IEEE NetSoft Conference and Workshops, NetSoft 2016, Seoul, South Korea, June 6-10, 2016)
Elastic deployments of virtualized network functions~(VNF) can automatically scale the amount of used resources in relation to their workload. This is often done by starting new VNF instances or stopping old ones. A problem of these scale operations is that most network functions are stateful and their internal state is not automatically migrated when traffic is redistributed in the deployment. As a result, mechanisms are needed to exchange or migrate internal network function state between VNF instances. This paper presents a state management framework that creates a logically distributed state store on top of elastically deployed virtual network functions. We also introduce a novel programming model that provides both a local and a global view of the state to each VNF instance. We discuss the integration of our framework into existing network function virtualization architectures and compare the performance of our prototype to a centralized and a distributed state store solution.

Joint real-time scheduling and interference coordination for wireless factory automation - Auroux, Sébastien; Parruca, Donald; Karl, Holger (27th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communications, PIMRC 2016, Valencia, Spain, September 4-8, 2016)

MeDICINE: Rapid Prototyping of Production-Ready Network Services in Multi-PoP Environments - Peuster, Manuel; Karl, Holger; van Rossem, Steven (IEEE Conference on Network Function Virtualization and Software Defined Networks (NFV-SDN))
Virtualized network services consisting of multiple individual network functions are already today deployed across multiple sites, so called multi-PoP (points of presence) environments. This allows to improve service performance by optimizing its placement in the network. But prototyping and testing of these complex distributed software systems becomes extremely challenging. The reason is that not only the network service as such has to be tested but also its integration with management and orchestration systems. Existing solutions, like simulators, basic network emulators, or local cloud testbeds, do not support all aspects of these tasks. To this end, we introduce MeDICINE, a novel NFV prototyping platform that is able to execute production-ready network functions, provided as software containers, in an emulated multi-PoP environment. These network functions can be controlled by any third-party management and orchestration system that connects to our platform through standard interfaces. Based on this, a developer can use our platform to prototype and test complex network services in a realistic environment running on his laptop.

Monitoring and debugging using an SDK for NFV-powered telecom applications - v. Rossem, S.; Tavernier, W.; Peuster, Manuel; Colle, D.; Pickavet, M.; Demeester, P. (Proc. IEEE Conference on Network Function Virtualization and Software Defined Network (NFV-SDN), Demo Track)

Placement of Services with Flexible Structures Specified by a YANG Data Model - Dräxler, Sevil; Karl, Holger (Proceedings of the 2nd International IEEE Conference on Network Softwarization (NetSoft))
Network function virtualization and software-defined networking allow services consisting of virtual network functions to be designed and implemented with great flexibility by facilitating automatic deployments, migrations, and reconfigurations for services and their components. For extended flexibility, we go beyond seeing services as a fixed chain of functions. We present a YANG model for describing the service structure in deployment requests in a flexible way that enables changing the order of functions in case the order of traversing them does not affect the functionality of the service. Upon receiving such requests, the network orchestration system can choose the optimal composition of service components that gives the best results for placement of services in the network. This introduces new complexities to the placement problem by greatly increasing the number of possible ways a service can be composed. In this paper, we describe a heuristic solution that selects a Pareto set of the possible compositions of a service as well as possible combinations of different services, with respect to different resource requirements of the services. Our evaluations show that the selected combinations consist of representative samples of possible structures and requirements and therefore, can result in optimal or close-to-optimal placement results.

NetIDE: All-in-one framework for next generation, composed SDN applications - Gutierrez, P. A. Aranda; Rojas, E.; Schwabe, A.; Stritzke, C.; Doriguzzi-Corin, R.; Leckey, A.; Petralia, G.; Marsico, A.; Phemius, K.; Tamurejo, S. (2016 IEEE NetSoft Conference and Workshops (NetSoft))

A non-disruptive automated approach to update SDN applications at runtime - Marsico, Antonio; Doriguzzi-Corin, Roberto; Gerola, Matteo; Siracusa, Domenico; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Empowering network operating systems with memory management techniques - Doriguzzi-Corin, Roberto; Siracusa, Domenico; Salvador, Elio; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Delayed (de-)activation in servers with a sleep mode - Herlich, Matthias; Bredenbals, Nico; Karl, Holger (Sustainable Computing: Informatics and Systems)

SmarterPhones: Anticipatory Download Scheduling for Wireless Video Streaming - Dräxler, Martin; Blobel, Johannes; Dreimann, Philipp; Valentin, Stefan; Karl, Holger (Proceedings of the 2nd International Conference on Networked Systems (NetSys))
Video streaming is in high demand by mobile users. In cellular networks, however, the unreliable wireless channel leads to two major problems. Poor channel states degrade video quality and interrupt the playback when a user cannot sufficiently fill its local playout buffer: buffer underruns occur. In contrast, good channel conditions cause common greedy buffering schemes to buffer too much data. Such over-buffering wastes expensive wireless channel capacity. Assuming that we can anticipate future data rates, we plan the quality and download time of video segments ahead. This anticipatory download scheduling avoids buffer underruns by downloading a large number of segments before a drop in available data rate occurs, without wasting wireless capacity by excessive buffering.We developed a practical anticipatory scheduling algorithm for segmented video streaming protocols (e.g., HLS or MPEG DASH). Simulation results and testbed measurements show that our solution essentially eliminates playback interruptions without significantly decreasing video quality.

HybridTE: Traffic Engineering for Very Low-Cost Software-Defined Data-Center Networks - Wette, Philip; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
The size of modern data centers is constantly increasing. As it is not economic to interconnect all machines in the data center using a full-bisection-bandwidth network, techniques have to be developed to increase the efficiency of data-center networks. The Software-Defined Network paradigm opened the door for centralized traffic engineering (TE) in such environments. Up to now, there were already a number of TE proposals for SDN-controlled data centers that all work very well. However, these techniques either use a high amount of flow table entries or a high flow installation rate that overwhelms available switching hardware, or they require custom or very expensive end-of-line equipment to be usable in practice. We present HybridTE, a TE technique that uses (uncertain) information about large flows. Using this extra information, our technique has very low hardware requirements while maintaining better performance than existing TE techniques. This enables us to build very low-cost, high performance data-center networks.

SynRace: Decentralized Load-Adaptive Multi-path Routing without Collecting Statistics - Schwabe, Arne; Karl, Holger (Proceedings of the 4th European Workshop on Software Defined Networks (EWSDN 2015))
Multi-rooted trees are becoming the norm for modern data-center networks. In these networks, scalable flow routing is challenging owing to vast number of flows. Current approaches either employ a central controller that can have scalability issues or a scalable decentralized algorithm only considering local information. In this paper we present a new decentralized approach to least-congested path routing in software-defined data center networks that has neither of these issues: By duplicating the initial (or SYN) packet of a flow and estimating the data rate of multiple flows in parallel, we exploit TCP’s habit to fill buffers to find the least congested path. We show that our algorithm significantly improves flow completion time without the need for a central controller or specialized hardware.

Optimizing Software-Defined Networks using Application-Layer Knowledge - Wette, Philip

On Network Application representation and controller independence in {SDN - A. Aranda-Gutierrez, Pedro; Karl, Holger; Rojas, Elisa; Leckey, Alec (2015 European Conference on Networks and Communications, EuCNC 2015, Paris, France, June 29 - July 2, 2015)

Error characterization of multi-access point WSNs in an aircraft cabin - Blanckenstein, Johannes; Nardin, Cristina; Klaue, Jirka; Karl, Holger (IEEE International Conference on Communication, ICC 2015, London, United Kingdom, June 8-12, 2015, Workshop Proceedings)

Topology model to generate realistic latency for simulations - Schwabe, Arne; Karl, Holger (2015 IEEE International Conference on Communications, ICC 2015, London, United Kingdom, June 8-12, 2015)

Anticipatory Download Scheduling in Wireless Video Streaming with Uncertain Data Rate Prediction - Dräxler, Martin; Blobel, Johannes; Karl, Holger (8th IFIP Wireless and Mobile Networking Conference, WMNC 2015, Munich, Germany, October 5-7, 2015)

Extending Hadoop's Yarn Scheduler Load Simulator with a highly realistic network & traffic model - Wette, Philip; Schwabe, Arne; Splietker, Malte; Karl, Holger (Proceedings of the 1st IEEE Conference on Network Softwarization, NetSoft 2015, London, United Kingdom, April 13-17, 2015)

Flexible reassignment of flow processing-aware controllers in future wireless networks - Auroux, Sébastien; Karl, Holger (26th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communications, PIMRC 2015, Hong Kong, China, August 30 - September 2, 2015)

Efficient flow processing-aware controller placement in future wireless networks - Auroux, Sébastien; Karl, Holger (2015 IEEE Wireless Communications and Networking Conference, WCNC 2015, New Orleans, LA, USA, March 9-12, 2015)

Specification of Complex Structures in Distributed Service Function Chaining Using a YANG Data Model - Dräxler, Sevil; Karl, Holger (CoRR)

Dynamic Backhaul Network Configuration in SDN-based Cloud RANs - Dräxler, Martin; Karl, Holger (CoRR)

An Architecture for Energy-aware On-demand Mobile Network Management - Peuster, Manuel; Karl, Holger (Proceedings of the 5th Workshop on All Things Cellular: Operations, Applications and Challenges)
The increasing amount of mobile traffic leads to a significantly higher energy consumption of mobile networks that is mainly caused by the high number of required base stations. One recent solution for this is based on a two-layered network that uses long-range macro cells to provide a full coverage signaling overlay and short-range small cells for fast data transmissions. These small cells can be switched off when they are not needed and allow network-wide energy optimizations. This paper presents an architecture that extends existing mobile networks to integrate a small cell layer that supports on-demand cell activation. We discuss how additional small cells can be interconnected with existing core components and how they can be controlled by a resource management component. Finally, a Wi-Fi based proof of concept testbed implementation is presented that demonstrates the feasibility of the approach.

Dynamic network reconfiguration in wireless DenseNets with the CROWD SDN architecture - Auroux, Sébastien; Draxler, Martin; Morelli, Arianna; Mancuso, Vincenzo (2015 European Conference on Networks and Communications (EuCNC))

MaxiNet: Distributed Emulation of Software-Defined Networks - Wette, Philip; Dräxler, Martin; Schwabe, Arne; Wallaschek, Felix; Zahraee, Mohammad Hassan; Karl, Holger (Proceedings of the 2014 IFIP Networking Conference (Networking 2014))
Network emulations are widely used for testing novel network protocols and routing algorithms in realistic scenarios. Up to now, there is no emulation tool that is able to emulate large software-deﬁned data center networks that consist of several thousand nodes. Mininet is the most common tool to emulate Software-Deﬁned Networks of several hundred nodes. We extend Mininet to span an emulated network over several physical machines, making it possible to emulate networks of several thousand nodes on just a handful of physical machines. This enables us to emulate, e.g., large data center networks. To test this approach, we additionally introduce a trafﬁc generator for data center trafﬁc. Since there are no data center trafﬁc traces publicly available we use the results of two recent trafﬁc studies to create synthetic trafﬁc. We show the design and discuss some challenges we had in building our trafﬁc generator. As a showcase for our work we emulated a data center consisting of 3200 hosts on a cluster of only 12 physical machines. We show the resulting workloads and the trade-offs involved.

Using Application Layer Knowledge in Routing and Wavelength Assignment Algorithms - Wette, Philip; Karl, Holger (Proceedings of the IEEE International Conference on Communications 2014)
Preemptive Routing and Wavelength Assignment (RWA) algorithms preempt established lightpaths in case notenough resources are available to set up a new lightpath in aWavelength Division Multiplexing (WDM) network. The selectionof lightpaths to be preempted relies on internal decisions of theRWA algorithm. Thus, if dedicated properties of the networktopology are required by the applications running on the network,these requirements have to be known to the RWA algorithm.We present a family of preemptive RWA algorithms for WDMnetworks. These algorithms have two distinguishing features: a)they can handle dynamic traffic by on-the-fly reconfiguration,and b) users can give feedback for reconfiguration decisions andthus influence the preemption decision of the RWA algorithm,leading to networks which adapt directly to application needs.This is different from traffic engineering where the network is(slowly) adapted to observed traffic patterns.Our algorithms handle various WDM network configurationsincluding networks consisting of heterogeneous WDM hardware.To this end, we are using the layered graph approach togetherwith a newly developed graph model that is used to determineconflicting lightpaths.

Tragedy of the Common Cloud - Game Theory on the Infrastructure-as-a-Service Market - Künsemöller, Jörn

Template Embedding: Using Application Architecture to Allocate Resources in Distributed Clouds - Keller, Matthias; Robbert, Christoph; Karl, Holger (Proceedings of 7th International Conference on Utility and Cloud Computing (UCC))
In distributed cloud computing, application deployment across multiple sites can improve quality of service. Recent research developed algorithms to find optimal locations for virtual machines. However, those algorithms assume to have either single-tier applications or a fixed number of virtual machines – a strong simplification of reality. This paper investigates the placement and scaling of complex application architectures. An application is dynamically scaled to fit both the current demand situation and the currently available infrastructure resources. We compare two approaches: The first one is based on virtual network embedding. The second approach is a novel method called Template Embedding. It is based on a hierarchical 1-allocation hub flow problem and combines applica- tion scaling and embedding in one step. Extensive experiments on 43200 network configurations showed that Template Embedding outperforms virtual network embedding in all cases in three metrics: success rate, solution quality, and runtime. This positive result shows that template embedding is a promising approach for distributed cloud resource allocation.

Specifying and Placing Chains of Virtual Network Functions - Dräxler, Sevil; Keller, Matthias; Karl, Holger (Proceedings of the 3rd International Conference on Cloud Networking (CloudNet))
Network appliances perform different functions on network flows and constitute an important part of an operator’s network. Normally, a set of chained network functions process network flows. Following the trend of virtualization of networks, virtualization of the network functions has also become a topic of interest. We define a model for formalizing the chaining of network functions using a context-free language. We process deployment requests and construct virtual network function graphs that can be mapped to the network. We describe the mapping as a Mixed Integer Quadratically Constrained Program (MIQCP) for finding the placement of the network functions and chaining them together considering the limited network resources and requirements of the functions. We have performed a Pareto set analysis to investigate the possible trade-offs between different optimization objectives.

Simulating load-dependent operation of picocells - Roeske, Daniel

Response Time-Optimized Distributed Cloud Resource Allocation - Keller, Matthias; Karl, Holger (Proceedings of the SIGCOMM workshop on Distributed cloud computing)
In the near future many more compute resources will be available at different geographical locations. To minimize the response time of requests, application servers closer to the user can hence be used to shorten network round trip times. However, this advantage is neutralized if the used data centre is highly loaded as the processing time of re- quests is important as well. We model the request response time as the network round trip time plus the processing time at a data centre.We present a capacitated facility location problem formal- ization where the processing time is modelled as the sojourn time of a queueing model. We discuss the Pareto trade-off between the number of used data centres and the resulting response time. For example, using fewer data centres could cut expenses but results in high utilization, high response time, and smaller revenues.Previous work presented a non-linear cost function. We prove its convexity and exploit this property in two ways: First, we transform the convex model into a linear model while controlling the maximum approximation error. Sec- ond, we used a convex solver instead of a slower non-linear solver. Numerical results on network topologies exemplify our work.

Reducing Energy Consumption of Radio Access Networks - Herlich, Matthias
Radio access networks (RANs) have become one of the largest energy consumers of communication technology [LLH+13] and their energy consumption is predicted to increase [FFMB11]. To reduce the energy consumption of RANs different techniques have been proposed. One of the most promising techniques is the use of a low-power sleep mode. However, a sleep mode can also reduce the performance. In this dissertation, I quantify how much energy can be conserved with a sleep mode and which negative effects it has on the performance of RANs. Additionally, I analyze how a sleep mode can be enabled more often and how the performance can be kept high. First, I quantify the effect of power-cycle durations on energy consumption and latency in an abstract queuing system. This results in a trade-off between energy consumption and latency for a single base station (BS). Second, I show that considering a network as a whole (instead of each BS individually) allows the energy consumption to be reduced even further. After these analyses, which are not specific for RANs, I study RANs for the rest of the dissertation. RANs need to both detect and execute the requests of users. Because detection and execution of requests have different requirements, I analyze them independently. I quantify how the number of active BSs can be reduced if the detection ranges of BSs are increased by cooperative transmissions. Next, I analyze how more BSs can be deactivated if the remaining active BSs cooperate to transmit data to the users. However, in addition to increasing the range, cooperative transmissions also radiate more power. This results in higher interference for other users which slows their transmissions down and, thus, increases energy consumption. Therefore, I describe how the radiated power of cooperative transmissions can be reduced if instantaneous channel knowledge is available. Because the implementation in real hardware is impractical for demonstration purposes, I show the results of a simulation that incorporates all effects I studied analytically earlier. In conclusion, I show that a sleep mode can reduce the energy consumption of RANs if applied correctly. To apply a sleep mode correctly, it is necessary to consider power-cycle durations, power profiles, and the interaction of BSs. When this knowledge is combined the energy consumption of RANs can be reduced with only a slight loss of performance. Because this results in a trade-off between energy consumption and performance, each RAN operator has to decide which trade-off is preferred.

Provider Competition in Infrastructure-as-a-Service - Künsemöller, Jörn; Brangewitz, Sonja; Karl, Holger; Haake, Claus-Jochen (Proceedings of the 2014 IEEE International Conference on Services Computing (SCC))
This paper explores how cloud provider competition inﬂuences instance pricing in an IaaS (Infrastructure-as-a-Service) market. When reserved instance pricing includes an on-demand price component in addition to a reservation fee (two-part tariffs), different providers might offer different price combinations, where the client’s choice depends on its load proﬁle. We investigate a duopoly of providers and analyze stable market prices in two-part tariffs. Further, we study offers that allow a speciﬁed amount of included usage (three-part tariffs). Neither two-part nor three-part tariffs produce an equilibrium market outcome other than a service pricing that equals production cost, i.e., complex price structures do not signiﬁcantly affect the results from ordinary Bertrand competition.

Incorporating feedback from application layer into routing and wavelength assignment algorithms - Wette, Philip; Karl, Holger (2013 IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS))

Anticipatory Power Cycling of Mobile Network Equipment for High-Demand Multimedia Traffic - Dreimann, Philipp

Adaptive Placement of Programmable Virtual Network Function Chains - Dräxler, Sevil

A Game-Theoretic Approach to the Financial Benefits of Infrastructure-as-a-Service - Künsemöller, Jörn; Karl, Holger (Future Generation Computer Systems)
Financial beneﬁts are an important factor when cloud infrastructure is considered to meet processing demand. The dynamics of on-demand pricing and service usage are investigated in a two-stage game model for a monopoly Infrastructure-as-a-Service (IaaS) market. The possibility of hybrid clouds (public clouds plus own infrastructure) turns out to be essential in order that not only the provider but also the clients have signiﬁcant beneﬁts from on-demand services. Even if the client meets all demand in the public cloud, the threat of building a hybrid cloud keeps the instance price low. This is not the case when reserved instances are oﬀered as well. Parameters like load proﬁles and economies of scale have a huge eﬀect on likely future pricing and on a cost-optimal split-up of client demand between either a client’s own data center and a public cloud service or between reserved and on-demand cloud instances.

Power model design for ICT systems -- A generic approach - Beister, Frederic; Dräxler, Martin; Aelken, J.; Karl, Holger (Computer Communications)

MAC Protocols for Cooperative Diversity in Wireless LANs and Wireless Sensor Networks - Azeem M. Khan, Rana; Karl, Holger (IEEE Communications Surveys and Tutorials)

Anticipatory power cycling of mobile network equipment for high demand multimedia traffic - Dräxler, Martin; Dreimann, Philipp; Karl, Holger (IEEE Online Conference on Green Communications, OnlineGreenComm 2014, November 12-14, 2014)

Flow processing-aware controller placement in wireless DenseNets - Auroux, Sebastien; Karl, Holger (25th IEEE Annual International Symposium on Personal, Indoor, and Mobile Radio Communication, PIMRC 2014, Washington DC, USA, September 2-5, 2014)

Using MAC addresses as efficient routing labels in data centers - Schwabe, Arne; Karl, Holger (Proceedings of the third workshop on Hot topics in software defined networking, HotSDN '14, Chicago, Illinois, USA, August 22, 2014)

Energy-efficient clock synchronization using wake-up receivers - Blanckenstein, Johannes; Karl, Holger (22nd International Conference on Software, Telecommunications and Computer Networks, SoftCOM 2014, Split, Croatia, September 17-19, 2014)

Predicting mobile video inter-download times with Hidden Markov Models - Beister, Frederic; Karl, Holger (IEEE 10th International Conference on Wireless and Mobile Computing, Networking and Communications, WiMob 2014, Larnaca, Cyprus, October 8-10, 2014)

Specifying and Placing Chains of Virtual Network Functions - Mehraghdam, Sevil; Keller, Matthias; Karl, Holger (CoRR)

DCT²Gen: A Versatile TCP Traffic Generator for Data Centers - Wette, Philip; Karl, Holger (CoRR)

Adding Geographical Embedding to AS Topology Generation - Schwabe, Arne; Karl, Holger (CoRR)